Clinical–insurer engagement to improve maternity safety in the UK, Ireland, Sweden and Australia. Issue 2 (April 2018) - Yau, Christopher W H; Quick, Oliver; Draycott, Timothy
Objective: To explore different models of clinical–insurer engagement around maternity safety and to understand how state insurers could and should engage with clinical staff to improve outcomes and reduce harm. Design: Semi-structured interviews and focus groups were conducted with senior representatives from state insurers. Transcripts were analysed to identify different models of engagement. Themes were also elicited from the transcripts. A further one-day focus group allowed for clarification and elaboration of these themes. Participants: Senior representatives from state insurers in England, Scotland, Wales, Republic of Ireland, Sweden and Victoria, Australia. Results: A variety of clinical engagement activities were undertaken by the insurers. These included training on claims and risk management, hospital site visits, facilitating multi-professional network meetings and working with clinical experts to develop best practice recommendations. Some insurers engaged with frontline clinical staff through collaborative patient safety programmes. The themes (identity and size, data and research, incentivising improvement and system integration) were important for considering the role of state insurers within health systems and how insurers could engage with clinical teams. Conclusions: This study identified different examples of clinical–insurer engagement. Whilst this was encouraging, the relationships between insurers and clinical teams could be developed further. Insurers and clinical staff could still collaborate more closely and work together in improving patient outcomes. Whilst not specifically their domain, insurers do have a role in patient safety. Closer clinical collaboration may strengthen this contribution.